No adverse effects of transgenic maize on population dynamics of endophytic Bacillus subtilis strain B916‐gfp. Issue 1 (25th September 2016) - Sun, Chongsi; Geng, Lili; Wang, Meiling; Shao, Gaoxiang; Liu, Yongfeng; Shu, Changlong; Zhang, Jie
Abstract: Endophytic bacterial communities play a key role in promoting plant growth and combating plant diseases. However, little is known about their population dynamics in plant tissues and bulk soil, especially in transgenic crops. This study investigated the colonization of transgenic maize harboring the Bacillus thuringiensis (Bt) cry1Ah gene by Bacillus subtilis strain B916‐gfp present in plant tissues and soil. Bt and nontransgenic maize were inoculated with B916‐gfp by seed soaking, or root irrigation under both laboratory greenhouse and field conditions. During the growing season, B916‐gfp colonized transgenic as well as nontransgenic plants by both inoculation methods. No differences were observed in B916‐gfp population size between transgenic and nontransgenic plants, except at one or two time points in the roots and stems that did not persist over the examination period. Furthermore, planting transgenic maize did not affect the number of B916‐gfp in bulk soil in either laboratory or field trials. These results indicate that transgenic modification of maize with the cry1Ah gene has no influence on colonization by the endophytic bacteria B916‐gfp present in the plant and in bulk soil. Abstract : Endophytic bacterial communities play a key role in promoting plant growth and combating plant diseases. This study investigated the colonization of cry1Ah Bt transgenic maize by Bacillus subtilis strain B916‐gfp, which is present in the plant tissues and surrounding soil. The results indicate that transgenic modification of maize with the cry1Ah gene has no influence on colonization by the endophytic bacteria B916‐gfp present in the plant and in bulk soil.